Diversity of Fishing Equipment for Fishermen in Gunung Kijang District, Bintan Regency - Azrianto, Frengky; Nevrita, Nevrita; Apdilah, Dony (Jurnal Perikanan dan Kelautan, 2021)
The increase in fishery production in Gunung Kijang District cannot be separated from fishing activities. The use of fishing gear that has the potential to damage the environment is assumed to be caused by public ignorance about the dangers of these tools. However, information about the diversity of types of fishing gear used by fishermen in Gunung Kijang District is still scarce. The purpose of the preparation of this scientific article is to provide information about the types of fishing gear used by the community in Gunung Kijang District, Bintan Regency. The preparation of this scientific article was carried out in April 2021 in Gunung Kijang District using a descriptive analysis based on a literature review using secondary data as a source of information. The fishing gear used by Gunung Kijang fishermen include mackerel nets, tuna, stingrays, corals, crabs, floating nets, motor boat charts, fish traps, crab traps, oval crab traps, fishing rods, longline fishing rods, spears, fish guns